PERSEPSI MASYARAKAT TERHADAP MANTAN NARAPIDANA - Novi Ismiasih (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
This study uses a qualitative descriptive research method. Data was obtained based on observation, interviews, and documentation. The location of the research implementation is in Glagahombo Village. Interview data were obtained from the community, ex-convicts, and families of ex-convicts, with the consideration that the selected informants knew and understood the problems to be studied. The results of this study indicate that the social interaction that is created between an ex-convict and the surrounding community needs to be done consistently. Because there are still people who have a negative opinion of ex-convicts, although there are also those who view them positively. If this continues, it is possible that ex-convicts will be mentally disturbed.